From Seizure Control to Parasite Management: Antiepileptic Drugs and Neurocysticercosis - Nagaraj, Abhishek Pete; Nagaraju, Purushotham Karadigere; Pasha, Thoppalada Yunus (International Journal of Pharmaceutical Investigation, 2026)
Epilepsy is a chronic brain condition that affects more than 65 million people worldwide, with 30% of patients unable to control seizures, despite progress in Antiepileptic Drugs (AEDs). This article exploring the history of AEDs, focusing on new AEDs such as cenobamate and fenfluramine, and it also explores the reason behind the withdrawal of certain drugs like felbamate, trimethadione, vigabatrin, and phenacemide. These withdrawals were primarily for some of the adverse effects, including liver failure, aplastic anemia, and visual disturbances that emerged after these drugs entered the market. The paper also addresses epilepsy caused by neurocysticercosis, a parasite infection from the tapeworm Taenia solium, discusses treatment strategies involving cysticidal drugs like praziquantel and albendazole, and along with prevention measures such as improved hygiene and vaccination. The paper emphasizes the importance of ongoing research for developing safer and more effective treatments.
Keywords: Cenobamate; Epilepsy; Felbamate; Neurocysticercosis; Trimethadione; Vigabatrin.